Development of Key Performance Indicators for the Improvement of University Facility Management Services in Korea. Issue 2 (1st May 2018) - Kim, Yujin; Kim, Min Soo; Kim, Jun Ha
Abstract : University facilities have significant effects on education and research and should be systematically maintained and managed. The Performance Indicator (PI) implicitly discloses the range of work scope and helps facility managers to achieve the goals and objectives of an organization. Much has been said about the importance of facility management (FM), however, there is no specific standard or guideline pertaining to FM services for campus facilities in Korea. Therefore, the main objective of this research is to provide facility managers with rigidly selected PIs for improving the quality of FM service of campus facilities. PIs are collected through intensive analysis of primary literature related to FM services and educational facilities. The 44 preselected PIs fell into four areas as classified in the Balanced Scorecard (BSC) and the Delphi survey was conducted twice to identify Key Performance Indicators (KPIs). Finally, the importance-performance analysis (IPA) and Kendall′s W are used to analyze the results. The priority on all the 44 PIs was set by considering four sections in the Importance-Performance Analysis (IPA) and finalization of the total of 8 KPIs. This research will serve as a guideline for campus facility managers in making decisions for improving the quality of FM services.